Analysis Role of Exchange Rate, BI Seven Days Rate, Inflation and Gold Price on Return of ISSI (Indeks Saham Syariah Indonesia) - Mohammad Samsul Arifin; Rosye Zaena; Abdul Karim; Septiana Na’afi; Aziz (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The aim of the researchers to be achieved in this study, is to test and analyze the short-term effect of the inflation rate, the rupiah exchange rate, world gold prices, and interest rates on ISSI returns. Test and analyze the long-term effect of the inflation rate, the rupiah exchange rate, world gold prices, and interest rates on ISSI returns. Data analysis was carried out using the EVIEWS 10 application or program, because the author uses time series data. With good performance for analyzing time series data, the authors prefer to use this program, compared to SPSS. ECM testing is carried out when there is an indication of a long-term relationship using the Cointegration test. In order to conclude that a data is cointegrated, each variable must be stationary in a similar or the same order. Based on the discussion of the research results, it can be concluded that in the short term, there is only one variable that has a significant influence on the return of the Indonesian Sharia Stock Index (ISSI). The variable is the rupiah exchange rate. Meanwhile, the other three variables, namely inflation, world gold prices, and interest rates have no significant effect on ISSI returns. Meanwhile, in the long term, there are three variables that have a significant influence on ISSI returns. The three variables include the rupiah exchange rate, world gold prices, and interest rates. Meanwhile, the inflation variable in the long term also does not have a significant effect on ISSI returns.